Recovery of tropical marine benthos after a trawl ban demonstrates linkage between abiotic and biotic changes - Zhi Wang (Nature Portfolio, 2021)
Zhi Wang et al. compare benthic surveys before and after the bottom trawling ban in Hong Kong in 2012 and demonstrate abiotic changes in sediment as well as macrobenthos diversity. These results showed that benthic communities were less fragmented following the ban and indicate trawling bans as an effective measure to restore biodiversity to tropical coastal waters.